2017
DOI: 10.1590/18069657rbcs20150505
|View full text |Cite
|
Sign up to set email alerts
|

Organic Carbon and Physical Properties in Sandy Soil after Conversion from Degraded Pasture to Eucalyptus in the Brazilian Cerrado

Abstract: Soil is currently seen as the most relevant carbon sink and the most effective carbon stabilizer. In contrast, agriculture is the second largest C emitter, after burning of fossil fuels. This organic carbon (OC) introduced into the soil, mainly via organic matter (OM), is essential for several soil properties and plays an extremely important role in sandy soils. The objective of this study was to describe the changes in the amounts and pools of OC and the influence thereof on some physical soil properties in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 54 publications
3
9
0
3
Order By: Relevance
“…The TOC and CS content found in the uppermost soil layer (Table 1) is related to the input of residual phytomass from eucalyptus harvest, a recurrent response frequently reported in the literature (Costa Jr et al, 2012;Guan et al, 2015;Jesus et al, 2015;Marques et al, 2016;Sena et al, 2017). Below the surface, the increases observed in TOC and CS in deeper layers (0.20-0.60 m -Table 1) for the CTL and B coincide with the layer of greatest abundance of the root system in eucalyptus.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The TOC and CS content found in the uppermost soil layer (Table 1) is related to the input of residual phytomass from eucalyptus harvest, a recurrent response frequently reported in the literature (Costa Jr et al, 2012;Guan et al, 2015;Jesus et al, 2015;Marques et al, 2016;Sena et al, 2017). Below the surface, the increases observed in TOC and CS in deeper layers (0.20-0.60 m -Table 1) for the CTL and B coincide with the layer of greatest abundance of the root system in eucalyptus.…”
Section: Discussionsupporting
confidence: 56%
“…In a study on sandy soil, Soares et al (2017) found changes of greater magnitude in carbon stocks in the organic matter fractions in the 0.00-0.10 m soil layer due to the large contribution of the eucalyptus residual phytomass. The organic fraction of the soils do not have the same stability as the mineral fraction under agricultural use; thus, intensive use of the soil can contribute to its degradation (Six and Paustian, 2014;Sena et al, 2017), compromising the stability of its aggregates. Consequently, losses of TOC occur, which increases soil bulk density and reduces total porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Manejos não-conservacionistas do solo, sob áreas de pastagem, podem promover a degradação da estrutura física, permitir a erosão, reduzir a macroporosidade e a infiltração de água, aumentar a resistência do solo à penetração de raízes, reduzir o volume total de poros do solo e promover erosão laminar (Byrnes et al, 2018;Brizzi et al, 2019). Estes processos acarretam no aumento da densidade do solo (Ds) e no menor desenvolvimento de macroagregados, culminando em uma contínua diminuição da produtividade (Sena et al, 2017). Entretanto, sistemas de manejo conservacionistas podem reverter este processo e melhorar os atributos físicos do solo, tais como a agregação e a Ds (Comin et al, 2016;Martinkoski et al, 2017).…”
Section: Introductionunclassified
“…Changes in soil use, from natural forest to agricultural use, frequently generate modifications in the soil organic carbon content. This affects the aggregates and soil stability directly, which leads to soil productivity loss (Sena et al, 2017). According to Lozano et al (1997), the soil structure and stability of aggregates are the most deteriorated physical properties in agricultural tropical soils that are exposed to intense conventional tillage.…”
Section: Introductionmentioning
confidence: 99%